2004
DOI: 10.1007/s00213-004-1971-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to nicotine replacement therapy versus quitting smoking among Chinese smokers: a preliminary investigation

Abstract: Clinically significant smoking cessation rates can be achieved among Chinese smokers in a clinic-based smoking cessation service. The NRT adherence was low and low adherence was associated with a lower quit rate. Trials of interventions to improve adherence and increase quit rates are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 33 publications
7
114
1
Order By: Relevance
“…In this study, only 36.6% of participants were adherent to recommended doses of nicotine gum, while 71.8% were adherent to attending required counseling sessions. Although there are no data regarding adherence to nicotine replacement or counseling among African Americans or light smokers, these results showing low adherence to nicotine gum are consistent with reports from the general populations 16,42 . In the current study, four predictors of adherence to gum therapy and one predictor of adherence to counseling were identified.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, only 36.6% of participants were adherent to recommended doses of nicotine gum, while 71.8% were adherent to attending required counseling sessions. Although there are no data regarding adherence to nicotine replacement or counseling among African Americans or light smokers, these results showing low adherence to nicotine gum are consistent with reports from the general populations 16,42 . In the current study, four predictors of adherence to gum therapy and one predictor of adherence to counseling were identified.…”
Section: Discussionsupporting
confidence: 84%
“…FTND = Fagerström Test for Nicotine Dependence. (Blondal et al, 1997;Garvey et al, 2000;Hajek et al, 1999;Hurt et al, 1997;Killen et al, 2004;Lam et al, 2005;Mooney et al, 2007;Schmitz et al, 2007;Shiffman et al, 2008). Adherence data for the COMPASS trial were collected prior to the Federal Drug Administration issuing a black box warning about possible neuropsychiatric symptoms associated with varenicline in 2009 and therefore may overestimate future adherence rates for this medication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extent to which an individual adheres to smoking cessation treatment medications has also been shown to be a critical factor in determining successful cessation among smokers (Blak, Wilson, Metcalfe, Maguire, & Hards, 2010, Catz et al, 2011, Cummings, Hyland, Ockene, Hymowitz, & Manley, 1997, Halperin et al, 2009, Lam, Abdullah, Chan, & Hedley, 2005, Piper et al, 2009Shiffman, Sweeney, Ferguson, Sembower, & Gitchell, 2008). In studies of MMT smokers, poor medication adherence has been identified as a significant barrier to successfully quitting Mooney et al, 2008;Richter et al, 2001;Stein et al, 2006Stein et al, , 2007.…”
Section: Quit Initiation and Treatment Adherencementioning
confidence: 99%